Udall visits library (Raton, New Mexico Raton Range)
Photograph includes Congressman Tom Udall, Director Thayla Wright, Assistant Librarian Angie Manfredi and staff member Tarin Quint. Photo taken by Frank Mahanna.
1 laminated newspaper article in the Raton Range.
Master list item #49
File location is in the Raton File Cabinet drawer 3
Keywords: Wright, Thayla -- Librarian -- Raton, New Mexico; Mahannah, Frank -- Photographer -- Raton, New Mexico; Udall, Tom -- Congressman -- Raton, New Mexico